Penerapan Peraturan Wali Kota Surakarta Nomor 16 Tahun 2020 Terhadap Inovasi Layanan Publik Bidang Perizinan Usaha - Purwono Sungkowo Raharjo; Asianto Nugroho; Aulia Putri Gandari (Hakim, 2024)
The government as a state administrator is obliged to provide services to the community by providing various information, facilities, and infrastructure to create responsive, solution and efficient public services. One of the ways this is realized is through the establishment of Public Service Malls (MPP). This research aims to find out how the Mayor's Regulation Number 16 of 2020 is implemented on public services in the field of business licensing in Surakarta through the One Stop Integrated Service (ONIS) model and what obstacles and efforts are made in innovating public services in the field of business licensing in improving service quality. in Surakarta. The research method used is empirical and uses a qualitative approach. In the Surakarta Public Service Mall DPMPTSP there are still obtacles, namely centralization of the OSS-RBA system by the center, lack of outreach to the community, and a lack of Human Resources (HR). DPMPTSP has also made efforts to overcome these obstacles, starting from holdingtraining, workshop, to the passivation of OSS-RBA socialization.